Türkiye’s Perspective Towards Lithuania and Lithuanian Tatars in the Framework of Cultural Diplomacy - Varışoğlu , Mehmet Celal; Varışoğlu, Behice (Lietuvos istorijos studijos, 2023)
In this study, the perspective of the Republic of Türkiye towards Lithuania and the Lithuanian Tatars has been examined within the framework of cultural diplomacy. The relations established within the cultural framework between the citizens of both countries contribute positively to the 92-year diplomatic relations of the two countries. Turkish Embassy in Vilnius in particular, Ministry of National Education, Ministry of Culture and Tourism, Turkish Cooperation and Coordination Agency (TIKA), Yunus Emre Institute, Presidency for Turks Abroad and Related Communities (YTB), universities, municipalities and other public institutions, companies, artists, academics, and students continue to contribute to the diplomatic relations between the two countries in the field of cultural diplomacy. In the study, it has been concluded that the historical and cultural bond between Türkiye and Lithuania continues to increase within the framework of public diplomacy and cultural diplomacy.